Factores psicosociales y su influencia en el comportamiento de un adolescente de 17 años agresor sexual - Rivera Chango, Vanessa Marilin (2021)
The present case study aims to analyze psychosocial factors and their influence on the behavior of a 17-year-old sexual offender. An evaluative process of evolutionary growth in the life cycle, the influence of the family and the social environment was carried out in one of the most conflictive main stages in the psychosexual development of adolescence. In the research methodology, access to Documented Information was obtained, the Clinical History and Psychological Report were used for data collection through the semi-structured interview, in addition to the application of the HTP Projection Test, Seapsi's Personality Questionnaire, where Characteristic personality traits were identified that satisfactorily influenced the diagnosis. During the case study, the presence of a Histrionic Personality Disorder was determined, fulfilling five of eight diagnostic criteria according to the DSM-5 and four of six symptoms. Treatment was proceeded through Cognitive Behavioral Techniques, obtaining favorable results in reducing the characteristic symptoms of the disorder.